A coupled bend-twist deformation monitoring method based on inclination measurement and rational cubic spline fitting. (15th January 2021) - Yu, Haoyu; Chen, Xiaolong; Ren, Mengyuan; Yin, Likang; Wu, Qian; Zhan, Jinsong; Liu, Qiang
Highlights: A novel parametric curve fitting function with an adjustable parameter k is introduced. A coupled bend-twist deformation monitoring algorithm based on two-time interpolation fitting and one-time coordinate transformation is developed. A prototype system that can eliminate the requirement of external excitation and a large number of sensors, but keeps high robustness and the potential in full scene applications of deformation monitoring is proposed. Abstract: Presented in this paper is a method for coupled bend-twist deformation monitoring of large-scale structures. A novel rational cubic spline fitting function with an adjustable parameter k is introduced. A coupled bend-twist deformation monitoring algorithm based on two-time interpolation fitting and one-time coordinate transformation is developed. A prototype monitoring system with several sensing and sink nodes, following the architecture of the IoT techniques, is constructed. The system together with the fitting algorithm can eliminate the requirement of external excitation and a large number of sensors, but keeps high robustness and the potential in full scene applications. Experimental testing has shown a 5% or better accuracy of the system under seven measurement inputs, which is consistent with theoretical simulation. The value law of the adjustment parameter k is revealed by both theoretical analysis and experiments. The effectiveness of the proposed method for coupled bend-twist deformation monitoring of large-scale structures on industrial sites has been proven by application testing. This study provides a potential solution for full scene monitoring of structures' deformation.